Formation of Adaptive Trophic Niches of Euryphagous Fish Species in Response to Off-Seasonal Water Level Regulation in Hongze Lake - Si Luo; Zexin Wang; Shengyu Zhang; Huan Mu; Yubin Jiao; Xiao Qu; Qishuo Wang; Ruiqi Yang; Yanxia Zuo; Shiyu Jin (Animals)
Off-seasonal water level regulations disrupt the biological traits and phenological rhythms of native fish species, yet their impacts on interspecific trophic interactions remain understudied. This study employed stable isotope analysis to assess the trophic dynamics of three fish species (Parabramis pekinensis, Carassius auratus, and Toxabramis swinhonis) across different water periods in Hongze Lake. The findings revealed that all three species occupied similar mid-level trophic positions, with no significant difference among water periods (p > 0.05). During high-water periods, P. pekinensis and T. swinhonis exploited broader niches, while C. auratus relied on a narrower diet. In contrast, during low-water periods, C. auratus expanded its niche, while P. pekinensis and T. swinhonis reduced their isotopic niche widths. Niche overlap analysis showed minimal trophic overlap among the three species during high-water periods, with increased overlap during low-water periods, except for the highest overlap between C. auratus and T. swinhonis during mid-water periods. This variation in niche overlap aligns with shifts in dietary reliance, as POM was the predominant dietary component for all three species, but its contribution varied significantly across different water periods. These findings indicated that adaptive trophic niche facilitated the coexistence of these fish species, while off-seasonal water level regulation may intensify interspecific competition. These insights are essential for refining water management policies and developing sustainable fishery management strategies of Hongze Lake and other water-level-regulated systems.